The theology of Paul's letter to the Romans - Haacker, Klaus (New Testament theology, 2003)
1. Introduction; 2. Theology in a nutshell; 3. Theology in process; 4. Major concerns; 5. Sorting the sources; 6. To the Romans a Roman?; 7. Romans in its canonical context; 8. The impact of Romans and interactions with Romans in church history; 9. The relevance of Romans reconsidered; Further reading.